1992
DOI: 10.1159/000107009
|View full text |Cite
|
Sign up to set email alerts
|

The Lupus Anticoagulant and Dementia in Non-SLE Patients

Abstract: The syndrome of circulating anticoagulants in patients without evidence of systemic lupus erythematosus (SLE) has lately become a focus of interest. The clinical features, neuroimaging findings and clinical course of 12 such patients, who presented with neurological symptoms, were analyzed. None of the patients fulfilled the American Rheumatism Association (ARA) criteria of SLE. During a follow-up period of up to 5 years, 9 patients (75%) deteriorated mentally. In 5, cerebrovascular lesions were observed clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…This proportion was significant when compared to age-matched controls. We also found that, in agreement with our previous observation [8], those who had high levels of aPLAb were elderly patients with DAT rather than with vascular dementia. It is expected that patients with high levels of aPLAb will develop vascular dementia and indeed, such a relationship was observed in younger stroke patients [11].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This proportion was significant when compared to age-matched controls. We also found that, in agreement with our previous observation [8], those who had high levels of aPLAb were elderly patients with DAT rather than with vascular dementia. It is expected that patients with high levels of aPLAb will develop vascular dementia and indeed, such a relationship was observed in younger stroke patients [11].…”
Section: Discussionsupporting
confidence: 93%
“…These antibodies are usually measured by binding to phospholipids in an enzyme-linked immunosorbent assay (ELISA) [1,2]. In this syndrome, as in systemic lupus erythematosus, the high levels of antiphospholipid antibodies (aPLAb) may be associated with neurological manifestations such as headache, stroke [3], chorea [4], epilepsy [5], psychosis [6] and dementia [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of circulating aPL IgG have been implicated in neurological diseases such as focal cerebral ischemia, myelopathy, Guillain-Barre syndrome, migraine, chorea, epilepsy and dementia (Lubbe and Walker 1983, Coull et al 1987, Levine et al 1987, Inzelberg and Korczyn 1989, Inzelberg et al 1992, Herranz et al 1994, Levine et al 1995, Cervera et al 1997. The pathogenesis of nervous system disease associated with aPL IgG is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study including 1,000 patients with APS, multi-infarct dementia was observed in 2.5% of patients, but no data were provided on subtle forms of cognitive dysfunction [15]. In other studies focusing on dementia and MRI, a significantly higher prevalence of dementia was observed [16,17].…”
Section: Cognitive Impairment and Antiphospholipid Syndromementioning
confidence: 95%